The Differences of Russian Life Styles in Leisure Time - Яна Михайловна Рощина (Journal of Economic Sociology, 2010)
With the help of R-TGI (Russian index of the targeted groups) data set the author defines eight different life styles of various social groups. Among them are sport, post-modern and many others.